Case-based discussion: neonates on extracorporeal membrane oxygenation for undiagnosed recalcitrant pulmonary hypertension—management challenges. Issue 1 (8th September 2022) - King, John A; Desai, Ajay; Semple, Tom; Nicholson, Andrew G; Bush, Andrew; Sonnappa, Samatha
Abstract : We present two neonates requiring extracorporeal membrane oxygenation for undiagnosed recalcitrant pulmonary hypertension, highlighting the clinical and ethical dilemmas in management of very rare diseases.